DYNAMICS OF CULTURAL INHERITANCE AND REPRODUCTION OF THE BUFFALO RACING FESTIVAL IN GLOBALIZATION AGE - พงศ์กิตติวิบูลย์ สุชาดา (Academic Journal Phranakhon Rajabhat University, 2018)
This research aimed to study the reproduction of a traditional buffalo racing including its roles and adaptation to the globalized world. This research utilized qualitative methodology together with interviews, and observation of practices and racing. The concepts of the reproduction of invented traditions and theories of functionalism were used as guidelines. The research found that (1) different buffalo racing advocacied differently affected the inheritance of the traditional buffalo races, (2) the reproduction of the buffalo race in the form of an invented tradition altered it from a spiritual event to a mundane one, (3) the collision between globalization and localism distributed the expansions of buffalo race, (4) globalization caused the reproduction of buffalo racing for tourism, (5) stakeholders in the reproduction of buffalo race were not limited to the locals anymore; public institutes took a major role (6) roles of the buffalo race in the globalized world was a spiritual anchor.